The role of english in the insurance business: A needs analysis model - Syakir, Syakir; Suhendar, Bagus (International Journal for Educational and Vocational Studies, 2022)
The purpose of this study is to find out a link and match between the need of English knowledge for people working in insurance business and insurance companies and the materials provided for STMA students learning English for Insurance as a model of a Need Analysis in English language learning and teaching, besides as a base for the module or book intended to write for the subject: English for Insurance. The objectives are: 1) to find out the percentage of the use of English in insurance business and insurance companies, 2) to find out the needs for Listening Skill, 3) to find out the needs for Speaking Skill, 4) to find out the needs for Reading Skill, 5) to find out the needs for Writing Skill, and 6) to find out the needs for English components (Grammar/Structure, Vocabulary, Insurance Terms). The need analysis approach used are those introduced by Hutchinson and Holet. The research methods used are simple quantitative using percentage, and qualitative and comparative methods to analyze and make conclusions. The research technique used is a questionnaire with 31 items for 6 issues, disseminated using google form with a link. The respondents are 38 people working in insurance business and insurance companies taking at random. The results show that: 1) English is used relatively high (from 38 respondents, 9 respondents say 50%, another 9 respondents say 75%, and even 1 says 100 %), 2) Listening Skill is relatively needed in their work (from 38 respondents, 24/63.12%-33/81.53% support the statements), 3) Speaking Skill is relatively needed in their work (from 38 respondents, 28 73.64%-33 /81.53% supports the statements).